Trails and paths From the south-central part of the province of Pamplona - Mejía-Molina, Alejandra; Villamizar-Solano, Ilich (Sello Editorial Unipamplona, 2025)
This book synthesizes and organizes information related to the trails and paths of the southern province of Pamplona and offers useful elements for defining a study itinerary, enabling us to gain an understanding of geomorphological and geological phenomena, and the geological evolution inherent to the processes that formed them. It contains current information on the current state of geological knowledge in the sector, organized through concise geological descriptions, illustrative diagrams, and conceptual and location maps. This book also includes previously unpublished photographic material and, in some cases, photogrammetric or geodetic products obtained through the survey of sections using unmanned aerial vehicles (drones). It also provides the reader with an insight into some of the cultural, historical, social, and economic processes of the builders and users of these provincial roads. It is in this spirit of harmonizing science and the joy of landscapes and heritage that the Paths and Trails series emerged, of which we now present the first itinerary. A geological journey through the south of the province of Pamplona—from the city of Pamplona—passing through Cácota de Velasco, Chitagá, and Santo Domingo de Silos.